PENGARUH INTERAKSI SOSIAL TERHADAP AKTIVITAS BELAJAR PESERTA DIDIK - Lia Rohanah; Mira Mirawati; Wawan Syahiril Anwar (Universitas Pakuan, 2020)
THE EFFECT OF SOCIAL INTERACTION ON STUDENTS LEARNING ACTIVITIESThis research uses quantitative research through a causal approach. The purpose of this study was to determine the effect of social interaction on student learning activities. The population in this study were grade IV students at Kebon Kalapa 01 Elementary School, Bogor Regency, even semester of the 2019/2020 academic year, totaling 82 students. The sample used was 45 students, which were obtained using the Taro Yamane formula. The validity test of the social interaction variable instrument and learning activities used the Pearson Product Moment formula and the reliability test used the Cronbach Alpha formula. Testing the requirements of the analysis in the form of normality test (liliefors), then carried out the homogeneity test (fisher). Data that has been declared normal and homogeneous is used to test the hypothesis, the results show that there is an effect of social interaction on student learning activities. The price of the regression coefficient Ŷ = 24.20 + (0.79X), this means that every one unit increase in social interaction variables will cause an increase in student learning activities by 0.79 units. The contribution of social interaction to the learning activities of students is shown by the correlation coefficient (rxy) of 0.82 tcount ttable (α = 0.05) = 9.3403 2.021 with a coefficient of determination 0.6724. This means that the increase or decrease in learning activities of students is influenced by social interaction by 67.24% while the remaining 32.76% is influenced by other factors. Based on the research results above, it can be concluded that there is a positive effect of social interaction on student learning activities.